PENGARUH PEMBERIAN CAMPURAN ABU SERBUK GERGAJI DENGAN PUPUK KANDANG AYAM DAN AIR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY - Hartika Wulan Sari; Islan Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the effect of the combination of sawdust ash and chicken manure along with water volume on the growth of oil palm seedling in the prenursery. The research also intended to determine the best dosage of ash and chicken manure combination and water volume application for seedling. This research was carried out at the Agriculture Experimental Station Faculty of Agriculture University of Riau for 4 months since March to July 2016. The research used Completely Randomized Design (CRD) consisted of 2 factors. First factor is combination of sawdust ash and chicken manure with three levels ( 10 g/plant, 20 g/plant, and 30 g/plant). Second factor is water application with three levels (100 ml/plant, 200 ml/plant, and 300 ml/plant). Combination of treatsment has 3 replications so that overall become 27 experimental units. Each experimental unit contains 2 seedlings Data obtained was analyzed by Analyis of Variance and further test using Duncan’s New Multi Range Test (DNMRT) at 5 % level. The combination of sawdust ash and chicken manure of 30 g/plant and the water application of 100 ml/plant has good influences on seedling height, stem diameter, and leaf area. Sawdust ash and chicken manure dosage of 30 g/plant good effect on seedling height, stem diameter and leaf area. Water of 100 ml/plant good effect on the number of leaf of oil palm seedling.  Kata kunci : Oil palm, sawdust ash, chicken manure, water.